Polyculture and Integrated Multi Trophic Aquaculture (IMTA) in Indonesia: A Review - Muhamad Dwi Cahya; Ayi Yustiati; Yuli Andriani (Torani Journal of Fisheries and Marine Science, 2021)
Polyculture is an aquaculture system that culture more than one species of fish in a single culture pond. The application of the concept of polyculture continues to develop rapidly and at its peak in the late 20th century, the application of integration in aquaculture activities resulted in a new polyculture system based on the integration of species with different trophic levels and having mutualistic relationships or better known as Integrated Multi-Trophic Aquaculture (IMTA ). Utilization of aquaculture waste from mainly species culture by secondary species is able to create an ecologically balanced aquaculture system, improve water quality, eliminate biological traces and provide better economic benefits compared to monoculture cultivation systems. Knowledge of trophic levels, feeding habits, placement of living space are things that must be mastered so that there is no competition between species that can cause failure in polyculture and IMTA activities. As developing science and public awareness of environmental quality generate demand for aquaculture activities can be more environmentally friendly and pay attention to aspects of sustainability of aquaculture activity. The Polyculture and IMTA systems are aquaculture systems that have the potential to be applied because they fulfill these two aspects.